Pulang kampung: communication technology network - Irwansyah, Irwansyah (Faculty of Communications Science, Dr. Soetomo University, 2020)
Pulang Kampung, popularly known as mudik bareng, is the activity or event of boro people. It means going back to their village. The activity allows many people to meet and gather with parents, extended families, and neighbours who have also travelled from their village and worked diversely at the migrant regions. This study focused on how one of the boro communities from Pule village at Jakarta mobilise their group members to the program using communication technology of cellular phone. This study applied the community mobilisation and coordination concepts which lead to the communication network model. The network model was analysed by density, centrality, and eigenvalue of social network analysis to depict the coordination and mobilisation map of communication technology network of cellular phone among the group member of boro community. In addition, the network was explored and discussed with types of kinship and community leadership.